Sulphate removal in industrial effluents using electrocoagulation sludge as an adsorbent - Yamba, Siyanda; Hintsho-Mbita, Nomso C.; Yusuf, Tunde L.; Moutloali, Richard; Mabuba, Nonhlangabezo (MDPI, 2022)
The high concentration of sulphates is detrimental to the infrastructure of wastewater treatment plants. Hence in this study, we present the application of electrocoagulation sludge as an adsorbent to remove sulphates from industrial effluents before they are released back to the environment. The sludge contains iron and aluminium cations and cationic complexes that precipitate sulphates in water. Corrugated iron sheet was used as a sacrificial electrode during electrocoagulation (EC) to generate sludge. FTIR, XRD, SEM, TEM, and Zeta Potential were used to characterize the sludge. The following parameters: contact time, pH, initial concentration, and adsorbent dosage were optimized to 120 min, 2, 100 mg/L and 150 mg, respectively. For the synthetic water, the sulphate removal was 99.1%, whereas for the real water it was found to be 98.7%. The adsorption capacity of the EC sludge was 66.76% for 2 h under acidic conditions. The Langmuir isotherm fitted better than the Freundlich isotherm. This confirmed the homogenous distribution of the active sites on the EC sludge. At different EC’s sludge, the pseudo-second order kinetic model produced the best fitting experimental results which confirmed the removal of sulphate ions by chemisorption. This approach (method) is useful for purifying industrial effluents before they are discharged into the environment.
Journal article published in Journal of Sustainability 2022, 14, 12467. https://doi.org/10.3390/su141912467
Keywords: Electrocoagulation sludge; Recycling; Wastewater treatment; Sulphates; Adsorbent; Calcium sulphate; Electrocoagulation; Sewage disposal plants